STAVROPOL DISTRICT COUNCIL DURING THE FIRST WORLD WAR - N. D. Sudavtsov (Гуманитарные и юридические исследования)
The article is devoted to the activities of Stavropol district council during the First World War. It had to adapt to the extreme conditions of the time. The article shows the effectiveness and efficiency of local self-government in spite of the short period of its functioning in the region.